Ecohome Sales Promotion Indonesia Giveaway in Building Brand Awareness - Ramadhan Alfa Rizki, Muhammad; Mujiono, Mujiono (Jurnal Komunikasi, Sains dan Teknologi, 2023)
Social media has now become part of people's lives. In addition, brands also use social media as a means of promotion, such as Ecohome on Tiktok and Instagram. Ecohome carries out activities that can build brand awareness. This study examines Ecohome Indonesia which uses Tiktok and Instagram as promotional media to build brand awareness. This research uses the concept of sales promotion and brand awareness. This research uses the post-positivism paradigm with a qualitative approach and data collection through interviews. The results of this study show that the strategy used by Ecohome Indonesia is to build community brand awareness through Tiktok and Instagram. Ecohome Indonesia utilizes social media platforms Tiktok and Instagram as a means of building public awareness.